PENGARUH PERMAINAN TRADISIONAL ENGKLEK TERHADAP KEMAMPUAN MOTORIK KASAR ANAK USIA 4-5 TAHUN DI TK ANANDA KECAMATAN TAMPAN KOTA PEKANBARU - Ledy Tiara; Zulkifli N '; Devi Risma (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Based on field observations of the gross motor skills of the students have not developed optimally. So that should be the application of the traditional game of hopscotch. This study aims to determine the effect of applying the traditional hopscotch game against the gross motor skills of children aged 4-5 years in kindergarten Ananda District of Tampan Pekanbaru. The sample used in this study 15 people protégé. The data collection techniques were used that observation and documentation. Data were analyzed using t-test using SPSS 16.0. The study hypothesis is the application of the traditional game of hopscotch can affect gross motor skills of children aged 4-5 years in kindergarten Ananda District of Tampan the city of Pekanbaru. It can be seen from the analysis of data obtained t = 15,466 and Sig. (2-tailed) = 0,000. Because Sig. (2-tailed) <0.05, it can be concluded that there are differences in gross motor skills significant protégé after using traditional hopscotch game. So it means Ho rejected and Ha accepted which means there is a very significant difference between before and after the experiment with applying traditional game of hopscotch. The influence of the traditional game of hopscotch on the gross motor skills of children aged 4-5 years in kindergarten Ananda Handsome District of Pekanbaru City 57.2%. Keywords: Gross motor skills, Traditional games hopscotch